Enhancing the Management of Hypersomnia: Examining the Role of the Orexin System - Morse, Anne Marie (Seminars in Neurology, 2025)
Excessive daytime sleepiness (EDS) is common. However, clinical features of excessive sleepiness can have broad and variable presentations. In addition, there can be an increased likelihood of medical or psychiatric comorbidity. Examination of the networks that regulate sleep–wake and circadian control reveals a complex and intricately designed integration system. Dysregulation in the coordination, effectiveness, or efficiency of these systems can contribute to developing EDS, and inform on the endotypes observed and pharmacologic considerations for treatment. The discovery and characterization of the diurnal expression and function of orexin (hypocretin) have led to a transformed understanding of sleep–wake control and EDS, as well as its role beyond sleep. As a result, a novel drug class, orexin agonists, is anticipated to emerge for clinical use in the near future. An understanding of orexin physiology and its transdisciplinary impact is necessary to best prepare for patient selection, use, and anticipated benefit and monitoring of both expected benefits and any other health change. This study provides a review of the range of clinical features and impact of EDS, the relationship between sleep–wake, circadian and other health networks, and an examination of orexin physiology with anticipatory guidance on the potential transdisciplinary role and impact of orexin agonists.
Keywords: narcolepsy; orexin; orexin agonists; sleepiness; cognition; hypersomnolence; idiopathic hypersomnia